CHEMICAL COMPOSITION OF PEAR FRUIT AND ITS IMPORTANCE IN TRADITIONAL MEDICINE - X.M. Noibjonova; O.Z. Qayumjonov; M.M. Qayumjonova (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Annotation. This scientific article presents a comprehensive analysis of the chemical composition of pear fruit, the biologically active compounds it contains, and their physiological and biochemical effects on the human body. In addition, the role of pear fruit in the digestive system, its influence on metabolic processes, and its applications in folk medicine are systematically described based on scientific literature and experimental data. The results of the study allow pear fruit to be evaluated as a functional food product with significant health benefits.